Impact of Technology Usage and Improved Teaching Styles on Effective Learning of Students: The Moderating Effect of Resistance to Change (Global Business Management Review (GBMR), 2019)
This study aims to empirically investigate and verify the impact of effective learning techniques that can help and aid in effective learning. This study tends to focus the education sector and tries to find out that how can students use advanced technology for the effective learning of students. In order to collect the data from the respondents, a survey method was conducted by distributing questionnaires in the students. 410 responses were collected using a non-probability convenience sampling technique. The data analysis was done by using SPSS (Statistical Package for Social Sciences). Findings show that resistance to change strengthens the positive relationship between the motivation of technology usage and student perception for effective learning. The results provide helpful information to the policymakers and academic institutes from which they could develop and improve appropriate strategies and provide essential assistance to the teachers in educational institutes.